Treatment of Granulomas in Patients With Ataxia Telangiectasia - Woelke, Sandra; Valesky, Eva; Bakhtiar, Shahrzad; Pommerening, Helena; Pfeffermann, L. M.; Schubert, Ralf; Zielen, Stefan (Frontiers in Immunology, 2018)
Background: Ataxia telangiectasia (A-T) is a devastating multi-system disorder characterized by progressive cerebellar ataxia, growth retardation, immunodeficiency, chronic pulmonary disease and chromosomal instability. Cutaneous granulomas are a known phenomenon in A-T but extra-dermal manifestation of granulomas at bone and synovia has not been reported so far. The clinical presentation, immunological findings, the long-term course and treatment options of eight patients with severe granulomas will be reported. Methods: From our cohort of 44 classical A-T patients, eight patients aged 2 to 11 years (18.2%) presented with granulomas. Immunological features of patients with and without granulomas were compared. Five patients suffered from cutaneous manifestation, in two patients we detected a bone and in one a joint involvement. Patients with significant extra-dermal involvement as well as one patient with massive skin manifestation were treated with TNF inhibitors. The patient with granulomas at his finger joint and elbow was treated with bone marrow transplantation (BMT). Results: Interestingly, seven of eight patients with granulomas were total IgA deficient, but there were no differences in IgG and IgM levels. All lymphocytes subsets were equally distributed except patients with granuloma had significantly lower naïve CD8 cells. In patients without treatment, four of eight showed a slow but significant enlargement of the granuloma. Treatment success with TNF inhibitors was variable. In one patient, treatment with TNF inhibitors led to a total remission for three years up to now. In two patients, treatment with TNF inhibitors led to a partial regression of granulomas. Treatment interruptions caused deterioration again. Conclusion: Granulomas in A-T progress slowly over years and can lead to significant morbidity. Treatment with TNF inhibitors was safe and in part successful in our patients. Interestingly BMT leads to complete remission, and indicates that aberrant immune function is responsible for granulomas in A-T patients.